Balancing socio-political acceptance and economic efficiency of electricity price signals for residential end users: lessons learnt from the pioneering Spanish experience - Batlle López, Carlos; Mastropietro, Paolo; Rodilla Rodríguez, Pablo; Navarrete Cruz, Diana María; Bello Morales, Antonio (My University, 2025)
The decarbonization of power systems would be more efficient if, among other developments, it would be possible to achieve a significant activation of electricity end users.But the political unwillingness to fully expose those later to market prices has been repeatedly proven worldwide, particularly when these prices are sustained in time, as for example it was evidenced during the energy price crisis that affected the European Union from 2021 to 2023. Thus, unavoidably, end-user retail prices design need to properly balance the orthodox pursuit of economic efficiency with the perennial sociopolitical perception of electricity supply as an essential service.Back in 2008, the Spanish National Energy Commission developed a ground-breaking electricity default tariff proposal to fully expose the country's nearly thirty million residential end users to hourly market prices. During the decade that followed, this methodology was gradually implemented, and was subject to deep controversy particularly during the referred energy crisis period, to the extreme to be subject to a new reform.We provide a detailed assessment of the evolution of this default tariff, a pioneering and unique real case example on how to widely and fully expose households to accurate market price signals, showing how residential consumers -and maybe more importantly politiciansreacted, and shedding also light on the main alternatives for future-proof tariff design.Among the many sound lessons that can be extracted, the pioneering Spanish experience shows how interventions in retail tariff design are not so much aimed at mitigating the cost of price volatility to end users, but rather at the significant risk aversion of governments in dealing with public opinion displeasure when these events occur.